Isolation, Identification, Characterization, and Plasmid Profile of Urinary Tract Infectious Escherichia coli from Clinical Samples. (20th March 2022) - Thangavelu, Sathiamoorthi; Dhandapani, Ranjithkumar; Arulprakasam, Ajucarmelprecilla; Paramasivam, Ragul; Chinnathambi, Arunachalam; Ali Alharbi, Sulaiman; Durairaj, Kaliannan; Shrestha, Anupama
Abstract : Objective . In recent times, urinary tract infection (UTI) is one of the most widely recognized bacterial diseases all over the planet. UTI influences individuals of any age and gender. The target of this study is to concentrate on the recurrence of uropathogens, the antimicrobial susceptibility pattern of the isolates, and the plasmid profile of people from the government clinics of Karaikudi. Methods . From July 2017 to December 2017, 100 urine tests were gathered and handled for the isolation of pathogenic microbes. In total, 89 isolates were found from the samples collected. Results . Escherichia coli was discovered as the most common bacterial isolate screened from the UTI-infected people, accounting for 28.09 percent of all isolates. E. coli was seen to be the highest prevalent bacterium for UTI in all age groups and demonstrated resistance to routinely used medications, especially cefpodoxime and novobiocin, which have been 100 percent resistant. The E. coli isolates screened were positive for beta-lactamase and film generation, and they have strong antimicrobial resistance. As a result, the E. coli strains with the highest prevalence of virulence determinants have become more resistant to many medications because they support the microorganism in overcoming the host's defense and colonizing or entering the urinary system. The amplified 16S rRNA product was analyzed, and phylogenetic relationships were determined. The presence of TEM (56 percent), CTX-M (64 percent), SHV (40 percent), and OXA (60 percent) was discovered. Among E. coli isolates, CTX-M was the most common extended spectrum-beta lactamase (ESBL). Multiplex PCR was also used to identify the existence of CTX-M subgroups in E. coli isolates. Conclusion . Finally, we urge that antibiotic selection should be predicated on the awareness of the specific prevalence and that novel antimicrobial medicines for urinary infections be developed to combat the overuse of antibiotics.